Media Sosial sebagai Sarana Penyebaran Kearifan Lokal Adat Minangkabau dalam Pelestarian Hutan Tropis Basah Harau - Nuari, Pasca Zenitho (Universitas Riau, 2018)
This research was conducted in Harau District, Limahpuluh Kota Regency, West Sumatera Province which has 270,5 Ha wet tropical forest on its hill which serves as a biological source with watershed (DAS) that can be utilized by the community. Biological sources such as flowers, fern-type vegetables, medicines, and some types of freshwater fish can be consumed or economic resources for the community. The source of water is used to irrigate the fields, as a tourist attraction waterfall, and swimming pool. Wet tropical forests also serve as a home for germplasm that can be used for scientific research of herbal medicines. The threat to destruction of the wet tropical forests of Harau is primarily gambier cultivation that can cause deforestation. Further damage can be caused by the taking of ornamental plants and flowers that is biodiversity reserves. This threat to forest destruction will obviously have a negative impact because of the effects of the loss of some forest trees and the biodiversity reserves of flowers, especially in areas with large ecological and biodiversity functions. According to the authors observation of this forest damage is about 10% (approximately 27 Ha) of forest area. Based on the research results it can be seen that the Harau people still use local wisdom and petitih petitih, pantun, talibun, gurindam, and tambo. Minangkabau custom in preserving wet tropical forest. The spread of local wisdom values in the past is done through generations of bakaba (oral information), custom speech, maota in lapau (chats in the shop), and surau (mosque) tradition. Socialization of local wisdom values according to the present condition is utilizing information technology/social media. In modern society, social media has a very real role as part of everyday human life, especially the younger generation. Spreading the values of local wisdom to conservation of wet tropical forest Harau through social media is considered the best to do in addition to the existing tradition. The values of local wisdom are not obsolete values that must be turned off, but can synergize with universal values and modern values. These issues can synergize with the actualization of the local philosophy of the Minangkabau community. Therefore, the dissemination of the values of Minangkabau custom local wisdom to preservation of wet tropical forest Harau can be done through social media.